The Students Errors in Using Punctuation in Descriptive Texts in the Fifth Grade (Mo 5) at Pratheep Vittaya School - Riski Angreini; Shoufi Nisma Dewi; Abdul Rahman Siagian; Muhammad Darwis; Nurmi Tayeh (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study was designed to examine the use of punctuation errors in the writing of 5th-grade students at Pratheep Vittaya. Students were recruited as samples for this study. To collect data, the researcher applied a mixed method, namely writing tests and interviews. The results of the study showed that comma omission was the most frequent error made by students (35 comma errors made by 11 students). Furthermore, this study sought the causes of errors made by students. The results found several factors that influence students to make errors in using punctuation: (1) Omission of some punctuation marks, (2) Lack of accuracy, (3) Misuse of the use of some marks, such as question marks and commas before quotation marks, (4) Misunderstanding the meaning of the text.